2012
DOI: 10.1177/1534735412463818
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Adenocarcinoma Cytotoxicity and Modulation of 7,12-Dimethylbenz[a]anthracene-Induced Mammary Carcinoma in Balb/c Mice by Acacia catechu (L.f.) Wild Heartwood

Abstract: The present data strongly suggest that anticancer potentiality of (+)-catechin-rich AQCE may be attributable to its ability to positively modulate tumor markers as well as the antioxidant system that could decompose the peroxides and, thereby, offer a protection against lipid peroxidation and linked to the expression of transcription factors during DMBA-induced mammary carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The conclusion from the three studies of Monga et al (, , ) is that an aqueous, catechin‐rich heartwood extract of A. catechu exhibits potent anticancer activity as demonstrated by the prevention of squamous cell, mammary, and liver cancers in a dose‐dependent manner.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion from the three studies of Monga et al (, , ) is that an aqueous, catechin‐rich heartwood extract of A. catechu exhibits potent anticancer activity as demonstrated by the prevention of squamous cell, mammary, and liver cancers in a dose‐dependent manner.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The authors also conducted a phytochemical screening of the extract as described in the Section on Chemistry. Monga et al (2011Monga et al ( , 2013 have conducted a series of studies on the chemoprotective effects of A. catechu hardwood extract in mice. In each of these studies, 7,12-dimethylbenz[a]anthracene (DMBA) or DMBA plus 12-O-tetradecanoylphorbol-13-acetate was used to induce tumors in the mice.…”
Section: Animal Studiesmentioning
confidence: 99%
“…(Fabaceae) also known as ‘Khadira’ has been extensively used as traditional medicine in India/Asia over a long period of time and a rich source of number of polyphenolic compounds. Previously, we have reported chemopreventive effect of aqueous extract of Acacia catechu in skin and mammary cancer rodent models [5,6]. (+)-Cyanidan-3-ol (CD-3) [3',4',5,7-tetrahydroxyflavan-3-ol] (Figure 1) is the most abundant polyphenolic flavonoid in the Acacia catechu heartwood and studies of the biological effects of CD-3 in cell culture and in vivo models indicated that this compound can inhibit lipid peroxidation [7].…”
Section: Introductionmentioning
confidence: 99%
“…One such polyphenol, which has attracted a lot of interest in the last few years is (+)-catechin (Fig. 18 At the same time, we reported the growth inhibition and apoptosis induction potential of (+)-catechin against hepatocellular 19 and breast carcinoma. The (+)-catechin is widely distributed in various plants like Camellia sinensis (tea) and Acacia catechu Willd.…”
Section: Introductionmentioning
confidence: 76%